Colour diversification in octocorals based on conjugated polyenes: A Raman spectroscopic view. (21st December 2012) - Maia, Lenize F.; de, Vanessa E.; Oliveira, Maria E. R.; Reis, Felipe D.; Fleury, Beatriz G.; Edwards, Howell G. M.; de, Luiz F. C.
<x xml:space="preserve">Abstract</x> Polyenic pigments in octocorals have been investigated by Raman spectroscopy using laser excitation at 532, 785 and 1064 nm. The spectral features suggest the structural nature of carotenoids from Phyllogorgia dilatata, Leptogorgia punicea, Muricea atlantica, Carijoa riisei and conjugated polyenals from L. punicea, L. setacea, Muricea flamma and Renilla muelleri. The observed vibrational bands at ca. 1540–1520 ν1(C=C), 1159 ν2(C–C) and 1005 cm−1 ρ3(C–CH3) were assigned to carotenoids, whereas the identification of non‐methylated conjugated polyenals have been proposed due to two major Raman bands at ca. 1500 and 1120 cm‐1, assigned to ν(C=C) and ν(C–C), respectively. Copyright © 2012 John Wiley & Sons, Ltd.